A model-driven approach to generate and deploy videogames on multiple platforms - Núñez-Valdez, Edward Rolando; García-Díaz, Vicente; Cueva Lovelle, Juan Manuel; Saez Achaerandio, Yago; González-Crespo, Rubén (Journal of Ambient Intelligence and Humanized Computing, 2017)
Currently, videogame development for mobile devices is a highly profitable and competitive industry worldwide. This profitability can be ascribed to the popularity that new technologies such as smartphones and tablets have acquired over the last few years. To increase competitiveness, we use a model driven engineering (MDE) approach to develop multi-platform videogames in a quick and easy manner. MDE helps us to reduce the number of errors, the amount of time required and the development costs and favors a productivity increment. The aim of this work is to present an approach for the agile development of multi-platform videogames by using high-level abstraction models. We offer a feasible solution supported by a tool that allows the development of videogames in a simple and agile way. An empirical validation is presented through a use case where the viability of our approach is shown in comparison with that of other tools. Finally, a survey shows the users' perception of the solution with the objective of validating the use case results. The given use case indicates that our approach is suitable for improving videogame development. The survey indicates that users think that it is possible to model videogames and generate the corresponding applications with our approach.
Keywords: model-driven engineering; software generation; user interface; videogames; JCR; Scopus